2019
DOI: 10.1007/s10494-019-00074-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Anisotropy on Turbulent Flow Over Irregular Roughness

Abstract: The influence of surface anisotropy upon the near-wall region of a rough-wall turbulent channel flow is investigated using direct numerical simulation (DNS). A set of nine irregular rough surfaces with fixed mean peak-to-valley height, near-Gaussian height distributions and specified streamwise and spanwise correlation lengths were synthesised using a surface generation algorithm. By defining the surface anisotropy ratio (SAR) as the ratio of the streamwise and spanwise correlation lengths of the surface, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 45 publications
7
21
1
Order By: Relevance
“…The levels attained by the wall-normal dispersive stresses (see figure 10 (b)) are also significantly lower than for the corresponding Reynolds stresses, an observation that is consistent with results for other irregular rough surfaces [69,70]. It is noticeable that the peak values of the wall-normal stress and the levels sustained above the maximum barnacle height are higher for the lower coverage surfaces, especially the 15% and 30% coverage cases.…”
Section: Reynolds and Dispersive Stressessupporting
confidence: 84%
See 2 more Smart Citations
“…The levels attained by the wall-normal dispersive stresses (see figure 10 (b)) are also significantly lower than for the corresponding Reynolds stresses, an observation that is consistent with results for other irregular rough surfaces [69,70]. It is noticeable that the peak values of the wall-normal stress and the levels sustained above the maximum barnacle height are higher for the lower coverage surfaces, especially the 15% and 30% coverage cases.…”
Section: Reynolds and Dispersive Stressessupporting
confidence: 84%
“…The peak spanwise Reynolds stresses (see figure 9 the peak location moves above the rough surface and a reduction of spanwise velocity fluctuations can be observed within the rough surface which is consistent with the decrease in the streamwise velocity fluctuations within the rough surface. In contrast to the results for the streamwise velocity component, the levels of the spanwise dispersive stresses are significantly lower, reaching peak values of less than 40% of the equivalent Reynolds stresses, which is comparable to the levels observed for other forms of irregular roughness [69,70]. As the coverage increases, the peak values first increase before attaining approximately constant levels for the 15% to 60% cases before decreasing again.…”
Section: Reynolds and Dispersive Stressescontrasting
confidence: 64%
See 1 more Smart Citation
“…In pure fluid turbulent flow, it has been found that surface anisotropy is an important parameter that influences skin friction and anisotropy of Reynolds stresses [6].…”
Section: Introductionmentioning
confidence: 99%
“…The case of isotropic roughness, where ES x = ES y , has been studied and extensively characterised for both regular [4] and irregular geometries [9]. Recent studies have shown that spanwise anisotropy strongly affects the near-wall region of the flow [2]. However, studies on the effect of anisotropy where the ratio ES x /ES y is systematically varied remain scarce.…”
Section: Introductionmentioning
confidence: 99%